Methodology for the use of software for the analysis of digital micrographs on the base of pathomorphology course in order to increase the professional level of students and scientists. - Poslavska, O. V. (Морфологія / Morphologia / Morfologìâ, 2015)
The article is devoted to the methodology of the use of software for the analysis of digital micrographs in pathomorphology on the example of calculation of the index of proliferation by immunohistochemical staining of samples with different plug-ins of "ImageJ". The purpose is to familiarize medical students, post-graduate students and researchers with modern computer technologies to enhance their professional level.